On Certain Generalized Weighted Mean Fractional Difference Sequence Spaces - Nayak, L.; Et, M.; Baliarsingh, P. (Natl Acad Sciences India, 2019)
The notion of the generalized difference operator () of order and the weighted mean operator G(u,v) are combined in the present article. Some related paranormed sequence spaces (u,v;(),p),c0(u,v;(),p),c(u,v;(),p) and (u,v;(),p), where is a positive real number, are also introduced. Certain topological properties are studied and Schauder bases of these classes are determined. Also, the -,- and -duals of these spaces via matrix transformations are computed.
Keywords: Difference operators Delta((alpha)), Delta(alpha) , Delta((-alpha)), Delta(-alpha); Generalized weighted mean operator G(u,v); Difference sequence spaces; alpha-, beta- and gamma-duals; Matrix transformations